Arbitration and Mediation: Resolution for Islamic financial problems in Malaysia: (Timbang Tara dan Pengantaraan: Penyelesaian Pertikaian Alternatif untuk Permasalahan Kewangan Islam di Malaysia0 (Kanun: Jurnal Undang-undang Malaysia, 2020)
Islamic finance is a financial system that operates according to Islamic principles. Some of the features found in the Islamic banking system are similar to those of the conventional banking system from the aspect of capital markets, fund managers, investment companies, and insurance companies. However, if there is a dispute related to Islamic finance, the parties involved will be referred to the courts. Nevertheless, the legal position in Malaysia indicates that any dispute arising in connection with Islamic financial transactions will be the jurisdiction of the civil courts and not the syariah court. Progress through the courts usually takes a long time and at high cost. Therefore, this study will identify alternative dispute resolution mechanisms for parties to resolve disputes without going to court. The method of alternative dispute resolution is seen as a solution that emphasizes the reduction of cost, time and expense to achieve progress in the field of Islamic finance. The study also provides brief information about some of the alternative dispute resolution methods (arbitration and mediation) in terms of features and their importance in resolving disputes relating to the Islamic financial system in Malaysia.Keywords: Islamic finance, alternative dispute resolution, arbitration and mediation